Kompetensi Sumber Daya Manusia dan Iklim Organisasi terhadap Kinerja Pegawai PDAM Tirta Pakuan Kota Bogor - Palahudin Palahudin; Ismartaya (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
This study aims to analyze the effect of human resource competence and organizational climate on employee performance in PDAM Tirta Pakuan, Bogor City. The population in this study were employees of the agency that were active. The sample in this study was 75 employees. Data collection method with a questionnaire. The value of the questionnaire was tested for validity and reliability before conducting further analysis techniques. Data analysis techniques in this study used the classic assumption test, multiple linear regression, multiple correlation, coefficient of determination and t & f test. The results of this study indicate from the results of hypothesis testing it can be concluded that the HR competency and organizational climate variables have a positive and significant effect on the employee performance. In answering hypotheses with simultaneous tests conducted by looking at the value of Fstat and Ftable where Fstat is 166.181 and Ftable is 1.96 with the assumption Fstat > Ftable, then H0 is rejected and H3 is accepted with the conclusion that there is a significant influence between HR Competency and Organizational Climate variables on Performance Employee Partially the independent variable also has a significant effect on the dependent variable with the calculated t value of the HR Competency variable of 4.678 and the Organizational Climate variable of 5.768 greater than the t table of 1.992 at a significant level ? = 0.05. Keywords: HR competency, organizational climate and employee performance